The acute physiological and perceptual effects of individualizing the recovery interval duration based upon the resolution of muscle oxygen consumption during cycling exercise - Fennell, C. R. J.; Hopker, J. G. (International Journal of Sports Physiology and Performance, 2021)
Purpose: There has been paucity in research investigating the individualization of recovery interval duration during cycling-based high-intensity interval training (HIIT). The main aim of the study was to investigate whether individualizing the duration of the recovery interval based upon the resolution of muscle oxygen consumption would improve the performance during work intervals and the acute physiological response of the HIIT session, when compared with a standardized (2:1 work recovery ratio) approach.